Posterior segment involvement in Infantile Nephropathic Cystinosis – A review - Keidel, Leonie Franziska; Schworm, Benedikt; Hohenfellner, Katharina; Kruse, Franziska; Priglinger, Siegfried; Luft, Nikolaus; Priglinger, Claudia (Klinische Monatsblätter für Augenheilkunde)
Cystinosis is a rare lysosomal storage disease with a prevalence of 1:100.000-1:200.000 cases. It is caused by biallelic mutations in the CTNS gene, which encodes cystinosin that transports cystine out of lysosomes. Due to its dysfunction cystine crystals accumulate in the lysosomes and ultimately cause apoptosis of the cell. Since cystinosin is ubiquitously present in the body, cystine crystals are deposited in every body structure and lead to the dysfunction of various organ systems in the course of time. Cystine crystals deposited in the cornea are a clinical hallmark of the disease, while there is less awareness of concomitant posterior segment alterations. Frequently, symmetrical pigment epithelial mottling and patches of depigmentation starting in the periphery, which progress towards the posterior pole, can be encountered upon fundus biomicroscopy. Spectral Domain Optical Coherence tomography (SD-OCT) represents an elegant tool for visualizing chorioretinal cystine crystals at the posterior pole. An SD-OCT-based clinical grading of the severity of the chorioretinal manifestation can potentially be applied as a biomarker for systemic disease status and monitoring of oral therapy adherence in the future. Along with previous histological examinations, it may also give information about the location of cystine crystals in the choroid and retina. This review aims to increase the awareness of vision-threatening retinal and choroidal changes in cystinosis and the concomitant findings in SD-OCT. Die Cystinose ist eine seltene, autosomal rezessiv vererbte lysosomale Speicherkrankheit der Aminosäure Cystin mit einer geschätzten Prävalenz von 1:100.000 bis 1:200.000. Ursächlich sind Mutationen im CTNS-Gen, welche für den lysosomalen Aminosäure-Transporter Cystinosin kodieren. Die Fehlfunktion des Cystinosins führt zu einer Akkumulation von Cystin im Lysosom und letztlich zur Apoptose der Zelle Das intrazelluläre Cystinosin ist ubiquitär im Körper vorhanden, sodass sich Cystin-Kristalle in jedem Gewebe ablagern und zu einer Dysfunktion verschiedener Organsysteme führen. Korneale Cystinkristallablagerungen sind pathognomonisch für die Erkrankung, während begleitende Veränderungen am hinteren Pol bislang weniger Beachtung fanden. Fundoskopisch sind häufig symmetrische retinale Pigmentepithelauflockerungen und depigmentierte Areale zu erkennen, die in der Peripherie beginnen und zum hinteren Pol fortschreiten. Die optische Kohärenztomografie (SD-OCT) eignet sich sehr gut zur Visualisierung chorioretinaler Cystinkristallablagerungen. Eine SD-OCT-basierte klinische Einstufung des Schweregrads der chorioretinalen Manifestation kann in Zukunft möglicherweise als Biomarker für den systemischen Krankheitsstatus und für die Überwachung der oralen Therapieadhärenz eingesetzt werden. In Zusammenschau mit früheren histologischen Untersuchungen können OCT-morphologische Aufnahmen Aufschluss über die genaue Lokalisation der Cystinkristalle in der Aderhaut und Netzhaut geben. Diese Übersichtsarbeit soll das Bewusstsein für visusbedrohende Netzhaut -und Aderhautveränderungen in der infantilen nephropathischen Cystinose und die begleitenden Befunde im SD-OCT schärfen.